2015
DOI: 10.1111/jfpp.12663
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing and Maintaining Nutritional Quality and Bioactive Compounds of “Hayward” Kiwifruit: Comparison of the Effectiveness of Different CaCl2 Spraying Times

Abstract: This study was conducted to elucidate the effect of calcium chloride (CaCl2) spraying times and number of sprays on the changes in biochemical compounds of “Hayward” kiwifruit (Actinidia deliciosa) during storage as well as at the shelf life. The vines in two different commercial kiwifruit orchards were sprayed with CaCl2 (15 g/L), one, two and three times in 35, 85 and 125 days after full bloom. Fruits were harvested at maturity stage and then were stored at 0C for 90 days and 5 additional days under simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Our findings are in line with those of Addai et al [24], who found that the amount of TPC had a significant effect on different harvesting stages of papaya fruits, and that the amount of TPC increased as maturity stages progressed. However, CaCl 2 increased the polysaccharide content in the fruit cell wall and maintained the strength of the cell membrane, which ultimately prevents the senescence-induced stress and delays the release or oxidize the phenolic compound from the fruit matrix [9]. Although the three-way interaction was non-significant, significant two-way relationships appeared between the harvesting stages × storage times and different levels of CaCl 2 × storage durations on DPPH.…”
Section: Total Phenolic Content (Tpc) and 22-diphenyl-1-picrylhydrazyl (Dpph)mentioning
confidence: 94%
See 1 more Smart Citation
“…Our findings are in line with those of Addai et al [24], who found that the amount of TPC had a significant effect on different harvesting stages of papaya fruits, and that the amount of TPC increased as maturity stages progressed. However, CaCl 2 increased the polysaccharide content in the fruit cell wall and maintained the strength of the cell membrane, which ultimately prevents the senescence-induced stress and delays the release or oxidize the phenolic compound from the fruit matrix [9]. Although the three-way interaction was non-significant, significant two-way relationships appeared between the harvesting stages × storage times and different levels of CaCl 2 × storage durations on DPPH.…”
Section: Total Phenolic Content (Tpc) and 22-diphenyl-1-picrylhydrazyl (Dpph)mentioning
confidence: 94%
“…Numerous physiological and biochemical mechanisms of tomato fruits were believed to be controlled by affiliation of calcium ion (Ca 2+ ) by declining the rate of respiration and ethylene production due to the increasing levels of Ca 2+ in the fruit matrix [8]. Therefore, the postharvest spraying with CaCl 2 showed higher in firmness, lower rate of ethylene and respiration; as a result, fruits showed the delay senescence [9].…”
Section: Introductionmentioning
confidence: 99%
“…This explains the increment of total phenol content recorded in our investigation. Moreover, calcium prevents senescence-induced stress by main¬taining the strength of its membrane 6 , and thus delays the release of phenolic compounds.…”
Section: Effect Of Cacl 2 Treatment On the Total Phenol Content In Tomatoes During Storagementioning
confidence: 99%
“…The rate of ethylene production and respiration in tomato fruits reportedly decreased by increasing the level of calcium ions 5 . Thus, treatment of fruits with CaCl 2 resulted in improving the firmness of the fruits and decreased deteriorations physiologically thereafter leading to reduced respiration, decrement in ethylene production, and delay in fruit ripening 6 . Various investigations revealed that calcium chloride treatment on tomato reduced post-harvest decay quantitatively in terms of development in the lycopene and ascorbic acid content, controlled development of physiological disorders, strengthening of the skin constituting cell walls, and providing the tissues with improved resistance, reduced production of enzymes which thus limit infections, control ripening, and rotting thus inevitably improving the quality and shelf-life of tomato 7 .…”
Section: Introductionmentioning
confidence: 99%
“…They reported that CaCl 2 decreased ethylene production and retained maximum phenolic content after 20 days of storage. Shiri et al (2016) reported that CaCl 2 increases the polysaccharide content in the fruit cell wall and maintains the strength of the cell membrane, which delays the release or oxidation of phenolic compounds from the fruit matrix. This is in-line with results obtained where the lowest reduction in TPC was found in the CaCl 2 treatment.…”
Section: 21mentioning
confidence: 99%